Role of Sex in the Therapeutic Targeting of p53 Circuitry - Mancini, Francesca; Giorgini, Ludovica; Teveroni, Emanuela; Pontecorvi, Alfredo; Moretti, Fabiola (Frontiers in Oncology, 2021)
Sex profoundly affects cancer incidence and susceptibility to therapy, with sex hormones highly contributing to this disparity. Various studies and omics data suggest a relationship between sex and the oncosuppressor p53 circuitry, including its regulators MDM2 and MDM4. Association of this network with genetic variation underlies sex-related altered cancer risk, age of onset, and cancer sensitivity to therapy. Moreover, sex-related factors, mainly estrogenic hormones, have been demonstrated to affect the levels and/or function of the p53 network both in hormone-dependent and independent cancer. Despite this evidence, preclinical and clinical studies aimed to evaluate p53 targeted therapy rarely consider sex and related factors. This review summarizes the studies reporting the relationship between sex and the p53 circuitry, including its associated regulators, MDM2 and MDM4, with a particular emphasis on estrogens. Moreover, we review preclinical studies and clinical trials to test whether sex effect of p53-target therapy has been reported and discuss the potential optimization of these therapies given patients' sex and hormonal status.